An alternative approach to estimate age‐related mortality of kidney transplant recipients compared to the general population: results in favor of old‐to‐old transplantations. (20th December 2013) - Foucher, Yohann; Akl, Ahmed; Rousseau, Vanessa; Trébern‐Launay, Katy; Lorent, Marine; Kessler, Michèle; Ladrière, Marc; Legendre, Christophe; Kreis, Henri; Rostaing, Lionel; Kamar, Nassim; Mourad, Georges; et al.
Summary Compared to dialysis, kidney transplantation appears to be the best treatment for chronic kidney failure, even for older aged patients. Nevertheless, the individual benefit of transplanting elderly patients has to be balanced against the corresponding increase in the number of patients awaiting grafts. We analyzed the excess mortality related to kidney transplant recipients by taking into account the expected mortality of the general population (additive regression model for relative survival). We applied this method to a cohort of patients who received a first deceased‐donor kidney transplant between 1998 and 2009 in France (DIVAT, n = 3641). Overall 10‐year mortality was 13%. As expected, recipient age was the main risk factor associated with overall mortality. In contrast, recipient age was no longer significantly associated with the excess of mortality related to kidney transplant status by subtracting the expected mortality of the general population. Delayed graft function (DGF), pretransplantation immunization, and past history of diabetes appeared as the main risk factors of this higher mortality rate. Our results constitute a strong argument in favor of kidney transplantation, regardless of the patient's age. Preventing DGF may be more effective for decreasing the risk of death specifically attributable to the disease.